Marginal-internal adaptation and fracture resistance of CAD/CAM crown restorations - EVREN, BUKET; YILDIZ, COŞKUN; ÖZKAN, YASEMİN (JAPANESE SOC DENTAL MATERIALS DEVICES, 2013)
This study evaluated the marginal adaptation and fracture resistance of CAD/CAM-fabricated zirconia crowns luted using different luting agents. Twenty crown restorations were produced using IPS ZirCAD zirconium oxide blocks (IZC), and another 20 using Lava zirconium oxide blocks (L). Ten teeth were used as control. Luting agents used were an etch-and-rinse adhesive (Variolink II) and a self-etch adhesive (Multilink Automix). Internal and marginal adaptation was evaluated using silicone replica technique. Fracture resistance was evaluated using a compression test. Marginal discrepancy was 89.26 mu m for L crowns and 88.84 mu m for IZC crowns, and difference was statistically insignificant. However, L crowns showed significantly larger axial and occlusal gaps than IZC crowns (p<0.05). Fracture resistance of IZC-Multilink was higher than the other groups, although the difference was not significant. Results showed that CAD/CAM-fabricated crowns showed acceptable in vitro marginal discrepancies and fracture strengths.
Keywords: CAD/CAM; Crown; Internal adaptation; Marginal adaptation; Fracture resistance; FIXED PARTIAL DENTURES; ALL-CERAMIC CROWN; Y-TZP ZIRCONIA; SINGLE CROWNS; MOLAR CROWNS; STRENGTH; SYSTEMS; THICKNESS; COPINGS; LOAD